2015
DOI: 10.1016/j.neuropsychologia.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Impaired recognition of body expressions in the behavioral variant of frontotemporal dementia

Abstract: Progressive deterioration of social cognition and emotion processing are core symptoms of the behavioral variant of frontotemporal dementia (bvFTD). Here we investigate whether bvFTD is also associated with impaired recognition of static (Experiment 1) and dynamic (Experiment 2) bodily expressions. In addition, we compared body expression processing with processing of static (Experiment 3) and dynamic (Experiment 4) facial expressions, as well as with face identity processing (Experiment 5). The results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 61 publications
6
33
0
Order By: Relevance
“…They are components of various intrinsic brain networks such as the salience network [Seeley et al, 2007], comprising anterior cingulate cortex and anterior insula, the default or mentalizing network [Buckner et al, 2008], including precuneus, temporo-parietal junction, medial prefrontal cortex, and the temporal poles, the action observation network [Grafton, 2009], including occipito-temporal, parietal and premotor areas, and the limbic network [Yeo et al, 2011]. Furthermore, numerous behavioral studies have shown impaired emotion recognition in bvFTD patients, using faces [Baez et al, 2014;Bediou et al, 2009;Bertoux et al, 2015;Couto et al, 2013;Diehl-Schmid et al, 2007;Fernandez-Duque and Black, 2005;Keane et al, 2002;Kumfor et al, 2011;Lavenu et al, 1999;Lough et al, 2006;Miller et al, 2012;Rosen et al, 2002;Snowden et al, 2008;Virani et al, 2013], bodies [Van den Stock et al, 2015] and music [Downey et al, 2013;Omar et al, 2011] as test stimuli. To gain insights into the specific functions that individual brain regions perform during emotion perception, we investigated emotion processing in patients diagnosed with the behavioral variant of frontotemporal dementia (bvFTD).…”
Section: Introductionmentioning
confidence: 99%
“…They are components of various intrinsic brain networks such as the salience network [Seeley et al, 2007], comprising anterior cingulate cortex and anterior insula, the default or mentalizing network [Buckner et al, 2008], including precuneus, temporo-parietal junction, medial prefrontal cortex, and the temporal poles, the action observation network [Grafton, 2009], including occipito-temporal, parietal and premotor areas, and the limbic network [Yeo et al, 2011]. Furthermore, numerous behavioral studies have shown impaired emotion recognition in bvFTD patients, using faces [Baez et al, 2014;Bediou et al, 2009;Bertoux et al, 2015;Couto et al, 2013;Diehl-Schmid et al, 2007;Fernandez-Duque and Black, 2005;Keane et al, 2002;Kumfor et al, 2011;Lavenu et al, 1999;Lough et al, 2006;Miller et al, 2012;Rosen et al, 2002;Snowden et al, 2008;Virani et al, 2013], bodies [Van den Stock et al, 2015] and music [Downey et al, 2013;Omar et al, 2011] as test stimuli. To gain insights into the specific functions that individual brain regions perform during emotion perception, we investigated emotion processing in patients diagnosed with the behavioral variant of frontotemporal dementia (bvFTD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the patients' difficulties to integrate intentions and outcomes for moral judgment may be related to impairments in theory of mind. Deficits in this ability have been reported in bvFTD patients [52,54,61,63]. Given that the patients' moral judgments tended to focus on outcomes rather than intentions, their performance may have been influenced by mental-perspective-taking deficits.…”
Section: Discussionmentioning
confidence: 98%
“…The association between both variables should be explored in future research on bvFTD. In addition, bodily and facial emotion recognition is affected in bvFTD patients [63,64]. Emotion-processing deficits have been associated with moral judgment impairments [21,65], and key brain regions involved in emotion processing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…we are “standing up for the body” (de Gelder et al, 2010) and exploring body language reading in typical (Atkinson et al, 2004, 2012; Chouchourelou et al, 2006; Ikeda and Watanabe, 2009; Alaerts et al, 2011; Sokolov et al, 2011; Krüger et al, 2013; Actis-Grosso et al, 2015; de Gelder et al, 2015; for review, see Pavlova, 2017) and atypical development (e.g., Nackaerts et al, 2012; Strauss et al, 2015; Van den Stock et al, 2015; Vaskinn et al, 2016; Blain et al, 2017). …”
Section: Yes Look At Behavior!mentioning
confidence: 99%